Rural corner store owners' perceptions of stocking healthier foods in response to proposed SNAP retailer rule changes. (December 2018) - Haynes-Maslow, Lindsey; Osborne, Isabel; Jilcott Pitts, Stephanie; Sitaker, Marilyn; Byker-Shanks, Carmen; Leone, Lucia; Maldonado, Adriana; McGuirt, Jared; Andress, Lauri; Bailey-Davis, Lisa; Baquero, Barbara; Kolodinsky, Jane; et al.
Highlights: Explores barriers and facilitators to stocking healthy food in rural corner stores. Investigates increasing restrictions for stores participating in U.S. SNAP program. U.S. rural corner stores will likely need assistance with selling healthy food. Corner store owners feel there are benefits to participating in the SNAP program. Abstract: Purpose: To better understand rural corner store owners' perceptions about the then proposed U.S. Department of Agriculture's (USDA) Supplemental Nutrition Assistance Program (SNAP) Retailer Rule. Methods: We conducted 32 interviews with rural corner store owners across six states in response to USDA's proposed rule. We asked owners about potential barriers to and facilitators of stocking healthier foods. Findings: Among the interviews, there were six main themes discussed: (1) SNAP Retailer Rule definition concerns; (2) challenges to implementation; (3) facilitators to implementation; (4) perceptions of SNAP customers; (5) benefits of being a participating retailer in SNAP; and (6) concerns about the threat to the store's economic viability if required to carry additional healthier items in line with the proposed rule. Conclusions: Rural corner stores need help promoting healthier food options, appropriately handling perishable items, finding suppliers that can adhere to their food delivery requirements, and maintaining their SNAP retailer license. Recognizing the implementation challenges of stocking healthier foods for corner stores and presenting feasible solutions to them can improve the likelihood of successful passages of healthy food access policies and programs. Future policies or programs focusing on stocking healthier foods should take into consideration rural corner stores' unique geographic landscape and business practices.